Noise properties of HTS Josephson mixers at 345 GHz and operating temperatures at 20 K. - Scherbel, J. (IEEE Transactions on applied superconductivity)
The authors report on the mixing properties of high-temperature superconductor bicrystal Josephson junctions at 345 GHz and high-operating temperatures. A variable backshort and E-plane tuner enabled the control of impedance matching between the junction and the RF environment. The local oscillator frequency and intermediate frequency were 345 and 1.4 GHz, respectively. The double-side band (DSB) mixer noise temperature and the conversion efficiency were determined using the hot/cold method. The authors observed that the noise temperature was strongly dependent on the matching conditions. The lowest noise temperatures were observed for tuner positions supporting the formation of a subharmonic step which appeared between the zeroth and first Shapiro step. At T = 20 K they obtained a lowest DSB mixer noise temperature of 1003 K and a conversion efficiency of -1.2 dB. They have investigated the dependence of the noise temperature on the operating temperature in detail. The impact of resonances on the device performance will be discussed.